Theoretical investigation on a simple turn on fluorescent probe for detection of biothiols based on coumarin unit - Ma, Tianhao; Huang, He; Liu, Yuling; Peng, Yongjin (Frontiers in Chemistry, 2023)
The discovery of a simple and efficient detection method for biothiols would be scientifically significant due to the crucial role of them in various physiological processes. Recently, a simple fluorescent probe, DEMCA-NBSC, based on coumarin fragments, was developed by Ding et al., and provided an efficient way for real-time sensing of biothiols both in vivo and vitro. Theoretical insights to the fluorescence sensing mechanism of the probe were provided in this work. Details of the electron transfer process in the probe under optical excitation and the fluorescent character of the probe were analyzed using a quantum mechanical method. All these theoretical results could inspire the development of a highly convenient and efficient fluorescent probe to sense biothiols both in vivo and vitro.